The Effectiveness of Animation Videos to Improve the Ability to Order Numbers 1-50 for Children with Physical Impairment - Puja Permai Sari; Nurhastuti Nurhastuti; Mega Iswari; Johandri Taufan (Universitas Muhammadiyah Enrekang, 2024)
This research aims to improve the ability to order numbers 1-50 for children with physical impairments at SLB N 1 Pariaman by using Animation Video Learning media. Animation Video Learning Media functions to make it easier for students to remember the material for ordering numbers. This research uses a quantitative approach with experimental methods, namely Single Subject Research (SSR) and A1-B-A2 Design, and data is analyzed using visual graphs by entering data in graphs which are then analyzed based on conditions A1-B-A2. The results of research using animated video learning media can improve the ability to order numbers 1-50 for children with physical impairments at SLB N 1 Pariaman.